A Low Insertion-Loss 10-110 GHz Digitally Tunable SPST Switch in 22 nm FD-SOI CMOS - Ciocoveanu, Radu; Weigel, Robert; Hagelauer, Amelie Marietta; Issakov, Vadim (A Low Insertion-Loss 10-110 GHz Digitally Tunable SPST Switch in 22 nm FD-SOI CMOS, 2018)
This paper presents a wideband digitally tunable SPST switch based on the travelling-wave concept that has been realized in a 22 nm FD-SOI CMOS technology. The digital control for return loss is performed through mutual inductance switching. Small-signal measurement results show that the proposed SPST switch achieves a bandwidth of 10-110 GHz, with an insertion loss of 1.2 dB at 60 GHz and a 24 dB isolation at 60 GHz, whereas large-signal measurements show a 1-dB compression point of +7 dBm at 24 GHz. Furthermore, the 3 digital control bits allow tuning return loss center frequency by approximately 7 GHz. The chip core size is 0.12 mm x 0.15 m